Assessment of Physicochemical Parameters from Vermicompost of Eudrilus eugenae and Esienia foetida - Tambe*, R. S. (Recent Research in Science and Technology, 2011)
In present investigation attempt has been made to investigate the physicochemical parameters like pH, temperature, moisture, salinity, nitrogen, electrical conductivity, nitrate, phosphate, chemical oxygen demand (COD) and biological oxygen demand (BOD) from vermicompost of Eudrilus eugenae and Esienia foetida species. The shade of size 10x10 meter and height 1.98 meter was constructed for rearing Eudrilus eugenae and Esienia foetida species. The production of vermicompost was found better in Eudrilus eugenae than Esienia foetida.